Snake Venom Derived Molecules in Tumor Angiogenesis and its Application in Cancer Therapy; An Overview - Dhananjaya, B.L.; Sivashankari, P.R. (Current Topics in Medicinal Chemistry, 2015)
Snake venom is a complex mixture of biologically and pharmacologically active components, comprising hydrolytic enzymes, non-enzymatic proteins/peptides, and small amounts of organic and inorganic molecules. The venom components are known to vary with geographic location, season, species and age of the snakes. The role of the venom in the snake is not primarily for self-defense, but in prey immobilization and its subsequent digestion. Hence, several digestive enzymes in venoms, in addition to their hydrolytic activity have evolved to interfere in diverse physiological processes that help in the immobilization of prey/victim. As snake components are capable of modulating the physiological response of envenomated prey/victim, they show promise as potential pharmacological tools, as drug leads and in diagnostic applications. This, in a practical sense to be a reality has to be linked to the advances in toxinology that provide investigators with an understanding of the pharmacodynamics of toxins together with improved understanding of the etiology of many human diseases and identification of potential sites for therapeutic intervention. This review aims at providing an overview on snake venom toxins and their derivatives that have potential anti-angiogenic effects for cancer treatment. Some of the anti-angiogenic components of snake venom like Snake venom metalloproteinases (SVMPs), Disintegrins, Phospholipases A2 (PLA2), CType Lectins (CLP), Vascular Apoptosis inducing Proteins (VAP) and L-Amino Acid Oxidases (LAAO) are discussed. This review aims at giving an overall view of these molecules and their mechanism of action as an effective antiangiogenic agent towards the treatment of cancer.
Keywords: Therapeutic application